HDAC inhibition induces autophagy and mitochondrial biogenesis to maintain mitochondrial homeostasis during cardiac ischemia/reperfusion injury. (May 2019) - Yang, Jing; He, Jin; Ismail, Mahmoud; Tweeten, Sonja; Zeng, Fanfang; Gao, Ling; Ballinger, Scott; Young, Martin; Prabhu, Sumanth D.; Rowe, Glenn C.; Zhang, Jianyi; Zhou, Lufang; et al.
Abstract: Aims: The FDA-approved histone deacetylase (HDAC) inhibitor, suberoylanilide hydroxamic acid (SAHA, Vorinostat) has been shown to induce cardiomyocyte autophagy and blunt ischemia/reperfusion (I/R) injury when administered at the time of reperfusion. However, the precise mechanisms underlying the cardioprotective activity of SAHA are unknown. Mitochondrial dysfunction and oxidative damage are major contributors to myocardial apoptosis during I/R injury. We hypothesize that SAHA protects the myocardium by maintaining mitochondrial homeostasis and reducing reactive oxygen species (ROS) production during I/R injury. Methods: Mouse and cultured cardiomyocytes (neonatal rat ventricular myocytes and human embryonic stem cell-derived cardiomyocytes) I/R models were used to investigate the effects of SAHA on mitochondria. ATG7 knockout mice, ATG7 knockdown by siRNA and PGC-1α knockdown by adenovirus in cardiomyocytes were used to test the dependency of autophagy and PGC-1α-mediated mitochondrial biogenesis respectively. Results: Intact and total mitochondrial DNA (mtDNA) content and mitochondrial mass were significantly increased in cardiomyocytes by SAHA pretreatment before simulated I/R. In vivo, I/R induced >50% loss of mtDNA content in the border zones of mouse hearts, but SAHA pretreatment and reperfusion treatment alone reverted mtDNA content and mitochondrial mass to control levels. Moreover, pretreatment of cardiomyocytes with SAHA resulted in a 4-fold decrease in I/R-induced loss of mitochondrial membrane potential and a 25%–40% reduction in cytosolic ROS levels. However, loss-of-function of ATG7 in cardiomyocytes or mouse myocardium abolished the protective effects of SAHA on ROS levels, mitochondrial membrane potential, mtDNA levels, and mitochondrial mass. Lastly, PGC-1α gene expression was induced by SAHA in NRVMs and mouse heart subjected to I/R, and loss of PGC-1α abrogated SAHA's mitochondrial protective effects in cardiomyocytes. Conclusions: SAHA prevents I/R induced-mitochondrial dysfunction and loss, and reduces myocardial ROS production when given before or after the ischemia. The protective effects of SAHA on mitochondria are dependent on autophagy and PGC-1α-mediated mitochondrial biogenesis.